Low temperature heat capacity and sound velocity in fullerite C60 orientational glasses; Fullerenes, Nanotubes and Carbon Nanostructures; Vol. 25, iss. 11 - Barabashko M. S. Maksim Sergeevich (2017, 2017)
Title screen